KEY LINES TO IMPROVE COMPETITIVENESS OF SMALL INNOVATIVE BUSINESSES - K. Yu. Reshetov (Модернизация, инновация, развитие, 2016)
The study discusses the importance of small innovative businesses in the modern global economy. The article also deals with the key lines to improve their competitiveness, and the author makes the conclusion how spread and promising the strategies are in Russia.